PENGARUH KOMITMEN KEORGANISASIAN DAN KINERJA TERHADAP IKLIM ORGANISASI DAN IMPLIKASINYA PADA CAPACITY BUILDING BIRO SARANA PRASARANA POLDA SUMATERA SELATAN - Ahmad Azhari; Fakhry Zamzam; Luis Marnisah (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2020)
This research is to find out the effect of organizational commitment and performance on the organizational climate and its implications for capacity building in the South Sumatra Regional Police Sarpras Bureau. The number of samples used by 60 people from the South Sumatra Regional Police Sarpras personnel was taken by questionnaire, data processing using Statistical Product and Service Solutions (SPSS) software version 24.0. The results of the study showed that organizational commitment influenced the organizational climate positively and significantly with t counted 7,364> t. 2,000, the performance affected the organizational climate positively and significantly with t counted 2,054> t. Table 2,000, organizational commitment and performance together influence organizational climate with F. count 27.127> F. table 1,534, with R Square out put effect coefficient 47%, organizational commitment affects capacity building positively and significantly with count 3.451> t.table 2,000, performance influences capacity building positively and significantly with a count of 2,201> t.table 2,000, the organizational climate influences capacity building positively and significantly by calculating 1,882> t. 2,000 table and organizational commitment, performance, organizational climate jointly influences capacity building with F. count 16,136> F. table 1,534, with the R Square out put effect coefficient of 43.5%.